1978
DOI: 10.1161/01.cir.58.2.265
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac tamponade: hemodynamic observations in man.

Abstract: SUMMARY Hemodynamic studies were performed before and after pericardiocentesis in 19 patients with pericardial effusion. Right atrial pressure decreased significantly, from 16 ± 4 mm Hg (mean ± SD) to 7 ± 5 mm Hg in 14 patients with cardiac tamponade. This change was accompanied by significant increases in cardiac output (3.87 ± 1.77 to 7 ± 2.2 I/min) and inspiratory systemic arterial pulse pressure (45 ± 29 to 81 ± 23 mm Hg). The remaining five patients did not demonstrate cardiac tamponade, as evidenced by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
3

Year Published

1982
1982
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(77 citation statements)
references
References 30 publications
0
74
0
3
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][13][14][15] The present study demonstrates distinctive hemodynamic features and echocardiographic manifestations of experimental cardiac tamponade in the presence of ischemic left ventricular dysfunction. The absence of pulsus paradoxus and the altered manner in which the cardiac chambers are compressed aid our understanding of the pathophysiology of cardiac tamponade and its clinical signs.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][13][14][15] The present study demonstrates distinctive hemodynamic features and echocardiographic manifestations of experimental cardiac tamponade in the presence of ischemic left ventricular dysfunction. The absence of pulsus paradoxus and the altered manner in which the cardiac chambers are compressed aid our understanding of the pathophysiology of cardiac tamponade and its clinical signs.…”
Section: Discussionmentioning
confidence: 75%
“…Pulsus paradoxus and echocardiographic evidence of right atrial and right ventricular collapse are useful signs because they may differentiate hemodynamically insignificant pericardial effusion from cardiac tamponade.1-5 However, clinical observations suggest that pulsus paradoxus may be absent in patients with left ventricular dysfunction and elevated left ventricular filling pressure. 1,6 In addition, although it has been reported that right ventricular diastolic collapse is sensitive to alterations in ventricular load,7,8 little is known about the effects of left ventricular dysfunction on chamber collapse during cardiac tamponade. These gaps in our knowl-edge are particularly relevant in view of the increasing numbers of patients with cardiac tamponade and coexisting cardiovascular disease.9 Accordingly, we studied cardiac tamponade in an animal model of ischemia-induced left ventricular failure to test the hypothesis that pulsus paradoxus is not present when cardiac tamponade occurs with concomitant left ventricular dysfunction manifested by elevated left ventricular filling pressure.…”
mentioning
confidence: 99%
“…[33][34][35][36] The volume in any cardiac chamber can only increase when there is an equal decrease in the volume in other chambers. Thus, venous return and atrial filling predominantly occur during ventricular systole as the ejection of blood out of the right and left ventricles lowers cardiac volume and allows blood to enter the atria.…”
Section: Cardiac Tamponade Pathophysiologymentioning
confidence: 99%
“…More grad ual fluid accumulation, 'medical tamponade', permits time for complex cardiocirculatory mechanisms, includ ing increased blood volume, to support systemic arterial pressure for longer periods [1]. Although uncommon, grossly elevated blood pressure despite cardiac tampon ade is well known [3][4][5][6]. Exacerbation of pulsus para doxus by effective antihypertensive therapy has notewor thy physiologic implications.…”
Section: Discussionmentioning
confidence: 99%